Micronized corn and urea-liquid supplements in growing rations for calves - Bolsen, K.; Chyba, Leslie J.; Ibbetson, W. (Kansas State University. Agricultural Experiment Station, 2011)
In growing rations containing fescue hay, micronized corn + urea-liquid gave: (1) 20.5% faster gains and 11.5% more efficient gains than cracked corn + urea-liquid and (2) similar rate and efficiency of gains as cracked corn + soybean meal.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Corn; Urea; Rations